2022
DOI: 10.21037/tau-22-448
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive ureteral reimplantation or endoscopic management for primary obstructive megaureter: a narrative review of technical modifications and clinical outcomes

Abstract: Background and Objective: Primary obstructive megaureter (POM) has various courses in different age populations. Although open ureteral reimplantation (OUR) remains the standard treatment for symptomatic POM, it is highly invasive with potential complications. In recent years, minimally invasive ureteral reimplantation (MIUR), including laparoscopic ureteral reimplantation (LUR) and roboticassisted laparoscopic ureteral reimplantation (RALUR), and endoscopic management, such as double-J stent insertion, endour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Reviewing the literature, we found 110 patients with the association of PUJO and POM reported in 10 articles (Table 1) [3,[13][14][15][16][17][18][19][20][21][22]. The available literature showed that the diagnosis of double obstruction was carried out in 67.3% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reviewing the literature, we found 110 patients with the association of PUJO and POM reported in 10 articles (Table 1) [3,[13][14][15][16][17][18][19][20][21][22]. The available literature showed that the diagnosis of double obstruction was carried out in 67.3% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the literature, we found 110 patients with the association of PUJO and POM reported in 10 articles (Table 1) [3,[13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations